Fast determination of calcium concentration in the internal tissues of a single seed using laser-induced breakdown spectroscopy. Issue 37 (2nd August 2016) - Han, Pengcheng; Dong, Daming; Du, Xiaofan; Jiao, Leizi; Zhao, Xiande
Abstract : Laser-induced breakdown spectroscopy was used for the fast determination of calcium concentration in the internal tissues of a single seed. Compared with conventional methods, LIBS had obvious advantages, such as a little analysis spot, little ablation, high precision, and small influence on the seed vigor. Abstract : The measurement of nutritional elements in internal tissues is important in modern breeding; calcium has an important role in keeping the cell structure and cell metabolism. However, existing measurement methods require a large number of seed samples and a pretreatment procedure and cannot quickly provide the element content in a single grain seed. In this paper, with a single grain of corn, we studied the spectral data of its endosperm as well as its embryo through the seed epidermis according to the erosion characteristics of laser pulses and implemented the direct rapid quantitative detection of calcium content in different tissues in the seed. We studied the main emission characteristic spectral lines of the calcium element and established this quantitative regression model with the characteristic spectral line at 396.8 nm for the analysis of calcium. The detection limit reached 1.05 PPM (parts per million) and spectral acquisition took less than 1 second. The measurement results indicated that the LIBS method was consistent with the traditional AAS method. This study confirmed that the LIBS method could realize the measurements of element contents in different tissues of a single grain seed and might be applied in modern breeding due to its fast measurement, slight damage, and simple procedure without pretreatment.